Investigating the influence of pectin content and structure on its functionality in bio-flocculant extracted from okra. (1st August 2020) - Mao, Yujie; Millett, Rachael; Lee, Chai Siah; Yakubov, Gleb; Harding, Stephen E.; Binner, Eleanor
Graphical abstract: Highlights: Water offers superior performance of okra pectin extraction than acid and alkali. Homogalacturonan contributes strongly to the flocculating ability of okra extract. Polymer bridging mechanism underpins the flocculant action of okra extract. A linear relationship between flocculating ability and pectin structure was found. Abstract: Okra extract is known to have potential application as a bio-flocculant for wastewater treatment. However, no research to date has given insight into the components responsible for the flocculating ability of okra extract or its flocculating mechanism. The work presented here addresses this knowledge gap showing that pectin, especially pectin homogalacturonan (HGA) regions, appear to be the polysaccharides responsible for the flocculating ability of okra extract. The way pectin works in flocculation may be best explained by a polymer bridging mechanism. Specifically, a linear relationship between okra bio-flocculating ability and pectin homogalacturonan region to rhamnogalacturonan-I region weight ratio (HGA/RG-I) was found (y = 2.0x+47.6, R 2 = 0.93, when GalA content > 300 mg/g extract), which was also validated using commercial citrus peel pectin.